Effect of Low dose Isotretinoin on Lipid Profile and Liver enzymes in Acne Patients: A Cross Sectional Study - Jha, Ayush; Shrestha, Rima; Khadka, Anupa; Wagle, Ashmita (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Introduction: Oral isotretinoin remains the most clinically effective anti-acne therapy. However, a myriad of adverse effects are associated with isotretinoin use. Elevated liver enzymes and an altered lipid profile are well documented side effects of prolonged oral isotretinoin usage. Objectives: To assess the alteration in liver enzymes and lipid profiles of acne patients on isotretinoin therapy. Materials and Methods: The current prospective hospital based study, was carried out from September 2022 to December 2023, and included 150 patients with acne vulgaris on isotretinoin therapy. All consenting patients were then subjected to a detailed history and clinical examination. Subsequently, baseline Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Triglyceride (TG), Low density Lipoprotein (LDL), and High density Lipoprotein levels (HDL) levels were measured. Patients were then started on oral isotretinoin therapy at conventional dosages. Levels of ALT, AST, TG, LDL and HDL were repeated at 3- month and 6- month follow-up visits. A self-designed proforma was used to collect all relevant data. The collected data was analyzed as per standard statistical protocol. Repeated measures analysis of variance was used to compare means between 3 groups (baseline, 3-month, and 6-month values). Results with a p<.05 were considered statistically significant. Results: The mean age of patients was 22.31(±SD 4.44) years. Females comprised the majority of our study subjects (n = 95; 63.33%). Levels of Alanine (F2,226=30.73, p<.0005) and Aspartate transaminase (F2,232=13.13, p<.0005) were increased significantly at 3 and 6 month follow up visits. Levels of TG were, also, increased significantly at follow up visits (F2,239=14.45, p<.0005). Similarly, levels of low density lipoprotein increased significantly when compared to baseline levels (F1,215=38.43, p<.0005). High density lipoprotein levels were decreased significantly when compared to baseline levels (F1,209=105.83, p<.0005). Conclusion: Our study has highlighted the significant alterations that occur in liver function tests and lipid profiles in patients on isotretinoin therapy.